System and socio-cognitive determinants of student satisfaction in Pakistani higher education - Panhwar, Adnan Jahangir; Ali, Najma Imtiaz; Jamali, Aadil; Brohi, Imtiaz Ali (Institute for Excellence in Education and Research, 2025)
This paper, explore predictors of student satisfaction with online and offline education through the synthesis of Information System Success framework and Social Cognitive Theory into a customized application in a South Asian university setting. The data were measured using a 26-questionnaire on a sample of 443 undergraduates and post-graduates in three state universities in Jamshoro, Pakistan; the instrument reliability was measured using a pilot (n = 10) and a global Cronbach alpha 0.81. The measure model was confirmed using confirmatory factor analysis and a two-step structural equation modeling method was used to test hypothesized direct and conditional effects. Findings have shown that the quality of the system, information and service quality have a great impact on student satisfaction with information, service and information quality respectively and together have a large share of the explanatory variance in the result of evaluations. Moderation tests show that personal variables (e.g., self-efficacy, perceived competence) and environmental resources (e.g., connectivity, institutional assistance) substantiate the positive effect of good-quality systems and information on satisfaction, but behavioral self-regulation has found its possessive power in the current sample. These results highlight that technologies alone cannot achieve much, but contextual supports and learner preparedness are key factors that determine how much improvement in systems will manifest into improved experiences of learners. The implications to institutional policy, LMS and mobile design and capacity-building initiatives are discussed and directions of longitudinal and experimental validation given.